Sustained vasodilation after cold pressor test is an independent predictor of poor survival in primary AL amyloidosis. (3rd October 2022) - Patras, R; Georgiopoulos, G; Petropoulos, I; Theodorakakou, F; Delialis, D; Angelidakis, L; Gavriatopoulou, M; Dimopoulou, M A; Sianis, A; Maneta, E; Neofytou, O; Terpos, E; et al.
Abstract: Background: Primary AL amyloidosis is a rare yet lethal systemic disorder. Dysfunction of the autonomous nervous system due to disease-related nerve infiltration is a common manifestation of AL amyloidosis. Previously published own work indicated that AL patients present sustained paradoxical vasodilation in response to sympathetic stimulus, as assessed by cold pressor test (CPT). The clinical relevance of this finding is unknown. Purpose: We sought to investigate the relationship between CPT-induced vascular response and mortality in AL amyloidosis. Methods: We consecutively recruited 97 newly diagnosed patients with AL amyloidosis. CPT of the brachial artery was performed before treatment initiation. All measurements were assessed using high resolution ultrasonography (14.0Mhz multifrequency linear array probe, Vivid 7 Pro; General Electric Healthcare, Milwaukee, Wisconsin, USA). The maximum vasodilation of the brachial artery was measured during the sympathetic stimulus and 3 minutes after withdrawal (sustained response). All-cause mortality was defined as the primary end-point of the study. Results: Mean age was 66 years with prevalence of male gender. Sustained vasodilation (but not vasodilation during CPT) was associated with heart failure, NYHA stage, BNP and peripheral vascular involvement (p<0.05 for all). Sustained vasodilation after withdrawal of the sympathetic stimulus was significantly associated with mortality as assessed by Cox regression analysis (HR: 1.149, 95% CI 1.042–1.269, p=0.005). This association remained significant after adjustment for age, sex, systolic blood pressure (SBP), nerve involvement and Mayo stage (HR: 1.123, 95% CI 1.014–1.243, p=0.026). A sustained vasodilation ≥3.35% from pre-stimulus diameter was associated with shorter survival (log-rank test, p=0.022, Figure 1). No association between vasodilation during sympathetic stress and mortality was observed. Conclusions: In AL amyloidosis, sustained paradoxical vasodilation in response to sympathetic stimulus was associated with poor survival. The clinical utility of this index of vascular autonomic dysfunction as a potential prognostic and therapeutic biomarker in AL amyloidosis merits further investigation. Funding Acknowledgement: Type of funding sources: None.